Outcomes of neonates with congenital duodenal obstruction: A retrospective study - Sheeba Qamer; Gera Parshotam; Bulsara Max; Rao Shripada (Journal of Pediatric Surgery Open, 2023)
Background: Congenital duodenal obstruction (CDO) is a common cause of intestinal obstruction in newborn infants. There is limited information on growth and neurodevelopmental outcomes of infants with CDO. Recent studies have suggested that early commencement of enteral feeds facilitates early attainment of full feeds in surgical and very premature non-surgical infants. We aimed to describe the physical growth and one-year neurodevelopmental outcomes of infants with CDO, and to explore the association between time of commencement of enteral feeds and time to reach full feeds in CDO. Methods: Retrospective study (2002–2019). Results: A total of 76 infants were included. The median gestational age was 37.2 w (range: 25.7 to 40.8). There were four deaths, not directly related to CDO. The mean Z scores for weight at birth was -0.39 (SD 1.05) vs -1.18 (SD 1.07) at discharge (p<0.0001). The mean Z scores for head circumference at birth was -0.04 (SD 1.21) vs -0.43 (SD 1.23) at discharge (p = 0.021). Adequate catch up growth occurred by one year. The median Development quotient (DQ) on Griffiths Mental Developmental Scales at one year among 41 non-syndromic infants was 100 (IQR: 94 to 107). On multivariable analysis, each day delay in commencing feeds was associated with 6% increase in time to reach full feeds (adjusted and exponentiated beta coefficient: 1.06; 95% CI: 1.02 to 1.09; p = 0.001). Conclusions: Infants with CDO had significant postnatal growth restriction during hospitalisation. Neurodevelopmental outcomes were reassuring. Early commencement of enteral feeds in the postoperative period may facilitate early attainment of full feeds. Level of evidence: Level IV Prognostic study